Microstructure refinement by tool rotation-induced vibration in incremental sheet forming. (2017) - Lu, Bin; Li, Zhaohua; Long, Hui; Chen, Fei; Chen, Jun; Ou, Hengan
Abstract: This paper presents a study of employing tool rotation-induced vibrations in incremental sheet forming (V-ISF) to produce sheet metal parts with laminated ultrafine-grained structures. Non-axisymmetric tools were developed to generate tool vibration and surface shear deformation of sheet material during forming. Using the V-ISF process, magnesium sheets of AZ31 were formed to the hyperbolic cones and laminated ultrafine grains with higher micro hardness were obtained by tool generated low frequency vibrations with large amplitudes. To further investigate surface shear deformation induced during processing, the hole-deformation analysis of samples cut from the formed hyperbolic cones was performed. This study found that large surface shear deformation of the sheet and the tool vibration during incremental forming are the two key factors for the formation of laminated ultrafine grains. The developed V-ISF process has a great potential to produce sheet metal parts with refined grains and greater micro hardness.